1962
DOI: 10.1161/01.cir.26.5.1092
|View full text |Cite
|
Sign up to set email alerts
|

On the Plasma Membrane of Some Bacteria and Fungi

Abstract: The contents of bacterial cells can be reversibly pulled away. (plasmolyzed) from the wall by strong salt solutions. Bacterial "protoplasts"—living cells divested of their wall—shrink or swell with changing concentrations of solutes in their environment and burst when this concentration falls below a critical level. These observations have long suggested that the cytoplasm of bacteria is covered by a selectively permeable plasma membrane. In recent years electron microscopy has revealed the existence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1965
1965
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…For ultrastructure studies, the pellets from a 2-liter culture were transferred to glass weighing bottles and fixed. The fixation was done either for 2 hours in a I per cent osmium tetroxide solution, in pH 7.4 Veronal-acetate containing added sucrose (Caulfield, 1957), or for 1 hour in a 6.25 per cent solution of glutaraldehyde in 0.1 M sodium cacodylate, final pH 7.2 (Sabatini, Bensch, and Barrnett, 1963). Glutaraldehyde fixation was followed by an overnight wash in cold 0.1 M cacodylate, and in some instances this was followed by a second fixation in osmium tetroxide.…”
Section: Methodsmentioning
confidence: 99%
“…For ultrastructure studies, the pellets from a 2-liter culture were transferred to glass weighing bottles and fixed. The fixation was done either for 2 hours in a I per cent osmium tetroxide solution, in pH 7.4 Veronal-acetate containing added sucrose (Caulfield, 1957), or for 1 hour in a 6.25 per cent solution of glutaraldehyde in 0.1 M sodium cacodylate, final pH 7.2 (Sabatini, Bensch, and Barrnett, 1963). Glutaraldehyde fixation was followed by an overnight wash in cold 0.1 M cacodylate, and in some instances this was followed by a second fixation in osmium tetroxide.…”
Section: Methodsmentioning
confidence: 99%
“…Among the higher fungi, the Ascomycetes have characteristic "plaques," sometimes revealing a fibrillar texture and a complex subarchitecture consisting of two to three discs. Such polar plaques (some synonyms: centriolar plaque, centrosome, archantosome, centrosomal plaque) are either closely apposed to the outer nuclear membrane or to both (Wells, 1970;Beckett and Crawford, 1970;Zickler, 1970) or, as in the yeasts, are totally embedded into the envelope, thus resembling a porelike interruption filled with indistinct dense material (Moor, 1966(Moor, , 1967Robinow and Marak, 1966;McCully and Robinow, 1971;Moens and Rapport, 1971;Unger et al, 1971; for meiosis see Peters on et al, 1972). Such polar plaques serve not only as terminal foci of microtubular orientation for both the nucleoplasmic spindle apparatus and the cytoplasmic aster, but also, according to Zickler (1970), might be penetrated by such microtubules.…”
mentioning
confidence: 99%
“…Some authors have suggested that such polar plaques might represent a specialized pore complex (Robinow and Marak, 1966;Scalzi and Bahr, 1968;Unger et al, 1971;Peters on et al, 1972. However, in spite of the fact that at first view they can resemble porous interruptions in the perinuclear cisterna, the micrographs published do not allow one to visualize them as pore complexes as defined in the previous Sections.…”
mentioning
confidence: 99%
“…In these early micrographs, the two dense laminae of the unit membrane were not recognized because they were masked, on the inner side by dense cytoplasm and on the outer side by a component ascribed to the cell wall. Robinow (1962) found a double contoured (unit) plasma membrane in vegetative forms of B. mycoides. He mentioned that his best views of the membrane were obtained when the protoplast was pulled away from the cell wall by some means or other.…”
Section: Discussionmentioning
confidence: 95%
“…Actinomyces (Edwards & Gordon, 1962). Bacillus (Chapman, 1953;Tokuyasu & Yamada, 1959;Fitz-James, 1960;Van Iterson, 1961;Glauert et al, 1961;Vanderwinkel & Murray, 1962;Robinow, 1962). Lactobacillus (Glauert, 1962).…”
mentioning
confidence: 99%